Optimal dispatch method of virtual power plant considering electric vehicle V2G under the low carbon target - YU Zhuo; MEN Jinbao; WANG Jun; LYU Hai; OUYANG Hong (Dianxin kexue)
The low carbon target strategy has promoted the rapid growth of distributed energy resources, such as wind power and photovoltaics, and the increase of electric vehicles ownership. Considering the smoothing effect of vehicle to grid (V2G) on the output fluctuation of distributed energy generation, and improving the wind/photovoltaic consumption level, the virtual power plant (VPP) technology was used to achieve unified management of the two, and then the carbon emission of the whole life cycle of electric vehicles and distributed energy generation were combined to establish an optimization model targeting at optimizing the cost of system operation and the cost of carbon emission. The model was solved by particle swarm optimization algorithm. Imental analysis based on example model combined with real vas conducted. The experimental analysis results show that the optimization model can effectively schedule all elements of VPP, and use the charging and discharging of electric vehicles to improve the operation and carbon emission benefits. It may provide a technical reference for the safe and stable operation of the grid system under the background of the low carbon target.